Athenry Dominican Priory, north chancel wall, canopied tomb niche, tomb chest architrave - O'Donovan, Danielle (My University, 2008)
The tomb chest section of canopied tomb, edge moulding of chest with pinnacle to sinister and moulding of small traceried panel to dexter. Moulding comprises, from pinnacle: fillet, quarter roll, quarter roll, flat surface, quarter roll, flat surface, quadrant, right-angled rebate, hollow chamfer. This tomb niche, in its overall composition, is very like that under the tower at Ennis Franciscan Friary.
Canopied tomb
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Funerary monuments; Tracery (Architecture); Late Medieval; roll mouldings; mouldings, hollow